Licence d'Artistes présente Arthur Agrandi - Espace Nesle, Paris (Paris : Licence d'Artistes, 1995)
Bessette, Laure ; Chichlakova, Nelly ; Hams, Sid' Ali ; Lemoine, Frédéric ; Torres, Carlos ; Salcedo, Gustavo ; Aubrian, Christof ; Knoch, Stanislas
Arthur Agrandi, Espace Nesle, Paris, 15 juin - 15 juillet 1995
boek